2018
DOI: 10.1038/s41467-018-05342-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical ferumoxytol nanoparticles disrupt biofilms and prevent tooth decay in vivo via intrinsic catalytic activity

Abstract: Ferumoxytol is a nanoparticle formulation approved by the U.S. Food and Drug Administration for systemic use to treat iron deficiency. Here, we show that, in addition, ferumoxytol disrupts intractable oral biofilms and prevents tooth decay (dental caries) via intrinsic peroxidase-like activity. Ferumoxytol binds within the biofilm ultrastructure and generates free radicals from hydrogen peroxide (H2O2), causing in situ bacterial death via cell membrane disruption and extracellular polymeric substances matrix d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
153
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 43 publications
1
153
0
Order By: Relevance
“…Researchers have found a novel bio-medical application for ferumoxytol as a topical therapy for the common and prevalent bio-lm, which results in oral diseases. 108 A bio-nanocomposite of Carboxymethyl Starch (CMS)-Chitosan (CS)-Montmorillonite (MMT) has been designed to deliver Curcumin (Jahanizadeh et al). They used ionic gelation technique and examined its anti-biolm activities versus Streptococcus mutans.…”
Section: Dental Applications Of Nanomaterialsmentioning
confidence: 99%
“…Researchers have found a novel bio-medical application for ferumoxytol as a topical therapy for the common and prevalent bio-lm, which results in oral diseases. 108 A bio-nanocomposite of Carboxymethyl Starch (CMS)-Chitosan (CS)-Montmorillonite (MMT) has been designed to deliver Curcumin (Jahanizadeh et al). They used ionic gelation technique and examined its anti-biolm activities versus Streptococcus mutans.…”
Section: Dental Applications Of Nanomaterialsmentioning
confidence: 99%
“…Nanoparticles have good designability compared with traditional antibiotics, and specifically designed nanoparticles can prevent and treat oral biofilm infectious diseases through microecological modulation of the oral cavity flora and biofilms . The development of selective nanoparticles that regulate the microecological balance of oral pathogenic biofilms has become an important area of research.…”
Section: The Possible Influence Of Nanomaterials On Oral Microecologymentioning
confidence: 99%
“…Controlling the key metabolic environmental factors that induce the pathogenic transformation of multicell community, instead of blindly killing opportunistic pathogens, will more effectively maintain the original microecological balance. The most promising method for achieving this is surface modification of nanoparticles ( Figure ). Study has shown that highly specific targeting of the acidic pH in oral biofilms can be obtained by treating ferric oxide nanoparticles with a dextran coating.…”
Section: The Possible Influence Of Nanomaterials On Oral Microecologymentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are sometimes called "the sword of nanotechnology, " and taking lessons from cancer therapy, several methods have become available to generate ROS (Sun et al, 2014;Liu X. et al, 2019). ROS produced by different types of nanoparticles in combination with the addition of external H 2 O 2 (Gao et al, 2016;Liu et al, 2018;Naha et al, 2019) has been shown to be effective in biofilm eradication. However, the use of cascade reactions to counter bacterial infections through ROS production using endogenously present substrate, i.e., without addition of external H 2 O 2 , has not yet been extensively considered.…”
Section: Introductionmentioning
confidence: 99%